Boosting the Performance of Nitrogen‐Doped Mesoporous Carbon Oxygen Electrode with Ultrathin 2D Iron/Cobalt Selenides. Issue 20 (19th August 2020) - Hong, Xuekun; Xu, Yuyang; Wang, Ruyue; Du, Peng; Zhao, Zebi; Huang, Kai; Tang, Haolin; Liu, Yushen; Lei, Ming; Wu, Hui
Abstract: High‐performance and low‐cost oxygen electrode catalysts for rechargeable metal–air battery have been regarded as one pivotal issue for the ever‐increasing energy‐demanding devices like electric vehicles, domestic appliances, and consumer electronics. To develop an effective substitute of noble‐metal‐based catalysts, the modified nitrogen‐doped mesoporous carbon (NMC) is proposed as composite catalysts with a series of 2D transition metal selenides (MSe, M = Fe and/or Co) by liquid exfoliation, anchoring, and thermal activation. By varying the transition metal elements, CoSe@NMC is confirmed as the competitive alternative relative to the coupled commercial catalysts (IrO2 and Pt/C), with a comparable overpotential for oxygen evolution reaction at 10 mA cm −2 and positively shifted half‐wave potential for oxygen reduction reaction even after accelerated durability tests for 5000 cycles. Therefore, this postmodification strategy can promote further design toward the advanced electrode materials for other energy conversion and storage techniques. Abstract : A series of 2D MSe (M = Fe or Co) nanosheets modifying nitrogen‐doped mesoporous carbon show good electrocatalytic performances for OER and ORR. A regular pattern of enhancing activity emerges with Co replacing Fe in the 2D transition metal selenides gradually and CoSe@nitrogen‐doped mesoporous carbon is selected as new alternative for present catalysts, with competitive performance.